Low-temperature CO oxidation on Ag/ZSM-5 catalysts: Influence of Si/Al ratio and redox pretreatments on formation of silver active sites - Kolobova E. N. Ekaterina Nikolaevna; Pestryakov A. N. Aleksey Nikolaevich; Mamontov G. V. Grigory Vladimirovich; Kotolevich Yu. I. Yuliya I.; Bogdanchikova N. E. Nina Evgenjevna; Farias M. H.; Vosmerikov A. V.; Vosmerikova L. V.; Cortes C. V. (2016, 2016)
Title screen